Predictors of the ability of innovation in organizations: Systematic literature review [Predictores de la capacidad de innovación en las organizaciones: Revisión sistemática de literatura] (2016)
This proposal is part of a much larger work, this first phase allowed to answer about the determinants of innovation capabilities in organizations for this purpose the Systematic Literature Review (RSL) was adopted using different equations search. From a base of 530 articles they were finally selected 108. The revision allowed many different definitions of the concept, as well as to pinpoint the determinants of innovation capability. In the same way a model with predictors of this capacity was proposed.